Improving Students’ Reading Comprehension Through Short Stories: A Classroom Action Research at Tenth Grade of SMK Swasta Panca Dharma Padangsidimpuan - Sianipar, Shinta Debora; Mahrani; Sibuea, Erni Rawati; Siregar, Parlindungan (Yayasan Kajian Riset dan Pengembangan RADISI, 2025)
Reading comprehension is a fundamental skill in English language learning, yet many students continue to face challenges in understanding written texts. This study aims to improve students’ reading comprehension through the use of short stories as an instructional medium. The research was conducted at SMK Swasta Panca Dharma Padangsidimpuan using a Classroom Action Research (CAR) approach, which consisted of two cycles involving planning, action, observation, and reflection. The sample included 30 students from class X Akuntansi. Data were collected using pre-tests, post-tests, and classroom observations. The results showed a significant improvement in students’ reading comprehension. The average pre-test score was 43.67, increasing to 68.00 in post-test I, and reaching 80.00 in post-test II. The percentage of students achieving the Minimum Competency Criteria (KKM) increased from 20% to 83.33%. These findings indicate that the use of short stories can be an effective and engaging strategy to enhance reading comprehension in EFL classrooms.